Spatial Distribution Analysis of Disaster-Vulnerable Groups in Bantul Regency, Yogyakarta - Pahleviannur, Muhammad Rizal; Hizbaron, Dyah Rahmawati; Muta'ali, Lutfi (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2023)
This study aims to analyze the spatial distribution of the population of disaster-vulnerable groups in Bantul Regency in 2022. This study used secondary data from the Central Statistics Agency (BPS) with data on infants, toddlers, children, pregnant or breastfeeding mothers, people with disabilities, and the elderly. The collected data is then processed to determine the density intervals of high, medium, and low vulnerable groups. The study results are presented as a spatial distribution map of the density of vulnerable groups. The results showed that areas with a high density of vulnerable groups were in Kasihan and Piyungan sub-districts. Sites with a moderate density of vulnerable groups are in the Banguntapan, Sewon, Bantul, Jetis, and Imogiri sub-districts. Meanwhile, areas with low density of vulnerable groups are in Sedayu, Pajangan, Pleret, Dlingo, Pandak, Bambanglipuro, Srandakan, Pundong, and Sanden Districts. Mapping the spatial distribution of vulnerable group density can determine areas in Bantul Regency classified as highly vulnerable group density to be prioritized first, then medium to low vulnerable group density. Thus, this research can be helpful for Bantul Regency policymakers in carrying out earthquake disaster risk reduction programs for vulnerable groups referring to the results of spatial distribution maps, and it is hoped that this research can be implemented for other regions in Indonesia.Keywords: Spatial Distribution, Disaster-Vulnerable Groups, Bantul Regency.